Effect of Aluminum-Copper Foils Interlayer on Failure Modes and Mechanical Properties of Galvanize Steel Sheets Joints Using Resistance Spot Welding (University of Thi-Qar Journal for Engineering Sciences, 2022)
The purpose of this article is to investigate the influence of commercial pure (0.04 mm thick) AL-foil and commercial pure (0.1 mm) Cu-foil at the interface of lap-joint on the characteristics of welds galvanized AISil 005 steel after welding throughthe tensile-shear testing. It was discovered that raising the welding current increases the size of the fusion zone. Due to the low current of spot-welding, the welds failed in an interfacial manner. Increasing the welding current results in adequate weld size and encourages the failure mechanism of double pullout with enhanced mechanical characteristics. Nonetheless, a further increase in welding current resulted in metal ejection and a modification of the failure mechanism with diminished mechanical qualities.The size of the fusion zone was determined to be the most influential factor in determining the mechanical characteristics of AISil 005 spot welds. The use of an AL interlayer boosts the galvanized AISI 1005 steel's mechanical characteristics and weldability. Cu interlayer addition diminishes the mechanical properties and weldability of galvanized AISI 1005 steel because it causes steel solidification cracking.